Ghrelin immunohistochemistry of gastric adenocarcinoma and mucoepidermoid carcinoma of salivary gland - Aydin, S; Ozercan, IH; Dagli, F; Aydin, S; Dogru, O; Celebi, S; Guzel, SP (Taylor & Francis Ltd, 2005)
Ghrelin (G-HH) synthesized in several tissues including salivary and stomach glands stimulates appetite in humans by modulating neuropeptide Y neurons in the hypothalamic arcuate nucleus. Loss of appetite is one of the most important symptoms of stomach cancer. We conducted a study using immunohistochemistry to determine whether salivary glands and stomach cancer tissues produce ghrelin. We determined that negative ghrelin immunohistochemistry discriminates tumors from normal tissues and may therefore further our understanding of the clinically important problem of reduced food intake and anorexia in cancer patients. Radioimmunoassay analyses confirmed that cancer cells do not produce a G-HH peptide, whereas normal cells yield this peptide.
Keywords: gastric cancer; ghrelin; immunohistochemistry; mucoepidermoid carcinoma; salivary gland